Transcutaneous spinal cord stimulation combined with robotic-assisted body weight-supported treadmill training enhances motor score and gait recovery in incomplete spinal cord injury: a double-blind randomized controlled clinical trial - Comino Suárez, Natalia; Moreno, Juan C.; Megía García, Álvaro; del Ama, Antonio J.; Serrano Muñoz, Diego; Avendaño Coy, Juan; Gil Agudo, Ángel; Alcobendas Maestro, Mónica; López López, Esther; Gómez Soriano, Julio (BMC, 2025)
Background Although transcutaneous spinal cord stimulation (tSCS) has been suggested as a safe and feasible intervention for gait rehabilitation, no studies have determined its effectiveness compared to sham stimulation. Objective To determine the effectiveness of tSCS combined with robotic¿assisted gait training (RAGT) on lower limb muscle strength and walking function in incomplete spinal cord injury (iSCI) participants. Methods A randomized, double¿blind, sham¿controlled clinical trial was conducted. Twenty¿seven subacute iSCI participants were randomly allocated to tSCS or sham¿tSCS group. All subjects conducted a standard Lokomat walking training program of 40 sessions (5 familiarization sessions, followed by 20 sessions combined with active or sham tSCS, and finally the last 15 sessions with standard Lokomat). Primary outcomes were the lower extremity motor score (LEMS) and dynamometry. Secondary outcomes included the 10¿Meter Walk Test (10MWT), the Timed Up and Go test (TUG), the 6¿Minute Walk test (6MWT), the Spinal Cord Independence Measure III (SCIM III) and the Walking Index for Spinal Cord Injury II (WISCI¿II). Motor evoked potential (MEP) induced by transcranial magnetic stimulation (TMS) were also assessed for lower limb muscles. Assessments were performed before and after tSCS intervention and after 3¿weeks follow¿up. Results Although no significant differences between groups were detected after the intervention, the tSCS group showed greater effects than the sham¿tSCS group for LEMS (3.4 points; p = 0.033), 10MWT (37.5 s; p = 0.030), TUG (47.7 s; p = 0.009), and WISCI¿II (3.4 points; p = 0.023) at the 1¿month follow¿up compared to baseline. Furthermore, the percentage of subjects who were able to walk 10 m at the follow¿up was greater in the tSCS group (85.7%) compared to the sham group (43.1%; p = 0.029). Finally, a significant difference (p = 0.049) was observed in the comparison